Pedagogy of caring: taking care and learning with the family - Costa, Maurício Cardoso da (Rev Rene, 2004)
Home internment, although incipient, is being developed in health institutions related to SUS – Sistema Único de Saúde (United Health System), in some cases when it is feasible for the nurse to visit a patient at his/her home. One of the objectives is the reduction of costs. In Ceará, a state in the northeast of Brazil, home internment started with PID-HM – Programa de Internamento Domiciliar do Hospital de Messejana (Home Internment Program of the Messejana Hospital), nowadays called PAD – Programa de Assistência Domiciliar (Home Assistance Program) of the Secretary of Health of the State of Ceará – SESA, and many public hospitals are incorporating the programs by attending cases of chronic-degenerative diseases.